Evaluation of a Yoga-Based Mind-Body Intervention for Resident Physicians: A Randomized Clinical Trial - Julia Loewenthal MD; Natalie L Dyer PhD; Marla Lipsyc-Sharf MD; Sara Borden MBA; Darshan H Mehta MD, MPH; Jeffery A Dusek PhD; Sat Bir S Khalsa PhD (SAGE Publishing, 2021)
Background and Objective Mind-body interventions (MBIs) have been shown to be effective individual-level interventions for mitigating physician burnout, but there are no controlled studies of yoga-based MBIs in resident physicians. We assessed the feasibility of a yoga-based MBI called RISE (resilience, integration, self-awareness, engagement) for residents among multiple specialties and academic medical centers. Methods We conducted a waitlist controlled randomized clinical trial of the RISE program with residents from multiple specialty departments at three academic medical centers. The RISE program consisted of six weekly sessions with suggested home practice. Feasibility was assessed across six domains: demand, implementation, practicality, acceptability, adaptation, and integration. Self-reported measures of psychological health were collected at baseline, post-program, and two-month follow-up. Results Among 2,000 residents contacted, 75 were assessed for eligibility and 56 were enrolled. Forty-four participants completed the study and were included in analysis. On average, participants attended two of six sessions. Feasibility of in-person attendance was rated as 28.9 (SD 25.6) on a 100-point visual analogue scale. Participants rated feasibility as 69.2 (SD 26.0) if the program was offered virtually. Those who received RISE reported improvements in mindfulness, stress, burnout, and physician well-being from baseline to post-program, which were sustained at two-month follow-up. Conclusion This is the first controlled study of a yoga-based MBI in residents. While the program was not feasible as delivered in this pilot study, initial analyses showed improvement in multiple measures of psychological health. Residents reported that virtual delivery would increase feasibility.